VARIATION OF FOREST STRUCTURE AND BIOMASS ALLOCATION AMONG DEGRADATION LEVEL OF WEST KALIMANTAN PEATLAND FOREST - Dwi Astiani; Lisa M Curran; Mujiman .; Ruspita Salim; Nelly Lisnawati; Dessy Ratnasari; Deddy D Firwanta; Yadi Purwanto (Jurnal Silvikultur Tropika, 2016)
Tropical peatland forests in Indonesia are facing a lot of pressure, resulting increased deforestation and degradation ofintact forests. Both natural and anthropogenic cause of changes – concentrated in Sumatra and Kalimantan, Indonesia –has been reported as 3.4% y-1 from 1990 – 2010. Currently, only ~ 41% to 44% of the original peatland forests ofKalimantan left. As a result of both changes, degraded peatlands have altered their balance on their natural conditions androles, since degradation of forest cover is often a complex process with their own of ecological recovery. A study hasbeen executed to explore the effect of forest degradation on forest structure and their biomass allocation in coastalpeatland forest of Kubu Raya, West Kalimantan. Forty eight of a 50 x 50 m sized plots with variety of degradation levelwere assessed for their tree structure, density, stand biomass, and basal area and compared. Results show that forestdegradation shifted tree diameter 10-20 cm dominance on their biomass stocks to larger trees (>20 cm) and smaller one(5-10 cm). Forest structure seems in a good and normal shape from small tree to large one. It is indicated that highdegraded forest demonstrate a decline its biomass allocation, tree density per hectare, basal area on each level of foreststructures.Key words : basal area, peatland forest, stand biomass, tree structure, tree density.